2002
DOI: 10.4141/p01-040
|View full text |Cite
|
Sign up to set email alerts
|

Bromus-Poaresponse to defoliation intensity and frequency under three soil moisture levels

Abstract: Smooth brome (Bromus inermis Leyss.) and Kentucky bluegrass (Poa pratensis L.) are important herbage for livestock and wildlife in Aspen-Boreal ecosystems in central Alberta, but there is paucity of information on the relationship between soil moisture and defoliation regimes on herbage production in these ecosystems. In a greenhouse experiment, we evaluated the effect of Bromus-Poa defoliation frequencies (2 or 4 wk) and intensities (2.5, 7.5, or 15 cm above the soil surface) under three soil moisture regimes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…However, seasonal changes were highly significant with an overall decrease in crude protein concentration and an increase in NDF concentration and a reduction in OM digestibility. Donkor et al (2002) also showed that high frequency and severity of defoliation decreased NDF concentration and increased crude protein concentration on Bromus-Poa swards. This is consistent with the results of Korte et al (1984), who reported that the difference in accumulation of dead material between high and low severity grazing was reduced during a dry period through the presence of desiccated vegetative tillers on high grazing severity treatments.…”
Section: Sward Differentiation According To Frequency and Severity Ofmentioning
confidence: 87%
“…However, seasonal changes were highly significant with an overall decrease in crude protein concentration and an increase in NDF concentration and a reduction in OM digestibility. Donkor et al (2002) also showed that high frequency and severity of defoliation decreased NDF concentration and increased crude protein concentration on Bromus-Poa swards. This is consistent with the results of Korte et al (1984), who reported that the difference in accumulation of dead material between high and low severity grazing was reduced during a dry period through the presence of desiccated vegetative tillers on high grazing severity treatments.…”
Section: Sward Differentiation According To Frequency and Severity Ofmentioning
confidence: 87%
“…Inside the seabird colony, the lack of relationship between R / S and N stock is possibly due to other factors, such as limiting water availability, overruling the effect of N availability on the R / S ratio. Drought has been reported to be an important determinant of R / S ratios (Donkor et al, 2002;Gianoli et al, 2009;Dreesen et al, 2012) and water infiltration in Andosols is rapid compared to most other soils (Basile et al, 2003), especially when the C content is below 12 %, as is the case on Surtsey (Arnalds, 2008). Therefore, we attribute the absence of a clear nutrient influence on R / S ratio to an overruling effect of drought in all occurring nutrient situations.…”
Section: Shifts From Belowground To Aboveground Plant Biomassmentioning
confidence: 83%
“…Stacy and colleagues (2005) grazed horses in a cool-season grassland at a reclaimed coal mine during the time of smooth brome tiller elongation. Even at a moderate defoliation rate (7.5 cm vegetation height, 4 wks between clippings), maximum aboveground biomass production in a smooth brome-Kentucky bluegrass (Poa pratensis) sod was achieved (Donkor et al 2002). However, more research into grazing as a control method is needed, as previous research has largely focused on maximizing stocking densities while also maximizing smooth brome herbage yields (Donkor et al 2002).…”
Section: Grazingmentioning
confidence: 99%